Can debt monetisation be helpful for China's post-Covid recovery? Some empirical evidence - Ziyi Cao; Zhirong Ou (Cardiff University, Cardiff Business School, 2021)
A measure of the degree of debt monetisation is constructed for its impact on the business cycle to be studied in a standard VAR model. Debt monetisation is hardly expansionary, as it raises public demand that crowds out almost as much demand from the private sector. However, it generates ináation, presumably because of ináationary expectations. Nevertheless the impact of debt monetisation on the business cycle dynamics is trivial, due to the low efficiency of the monetary transmission mechanism. Unless policy proposals are for extraordinarily aggressive moves, or they are accompanied by monetary reforms which facilitate monetary transmission, the recent debate on debt monetisation, we argue, possesses more theoretical meaning than practical meaning for Chinaís post-Covid recovery.
Keywords: E31; E32; E63; H63; 330; Debt monetisation; business cycle; VAR; China